THE EFFECT OF CAREER DEVELOPMENT ON TURNOVER INTENTION MEDIATED BY JOB SATISFACTION AMONG HEALTHCARE WORKERS IN YOGYAKARTA - Rakesh Sitepu; Agus Suryanto Sukisman; Kurniawati Setyaningrum; Agus Pambudianto; Agung Budi Wibowo (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the effect of career development on turnover intention mediated by job satisfaction among healthcare workers in Yogyakarta. The research employs a quantitative approach with a causal research design. The study examines career development as the independent variable, turnover intention as the dependent variable, and job satisfaction as the mediating variable. The population of this study consists of healthcare workers in Yogyakarta, with a sample of 130 respondents. Data were collected using a questionnaire instrument measured on a Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, processed using SmartPLS version 3.0 software. The results indicate that career development has a positive and significant effect on job satisfaction, career development has a negative and significant effect on turnover intention, and job satisfaction has a negative and significant effect on turnover intention. Furthermore, the indirect effect analysis demonstrates that career development has a negative and significant effect on turnover intention through job satisfaction, confirming the mediating role of job satisfaction in the relationship between career development and turnover intention among healthcare workers in Yogyakarta.